The Predictive Strength of the End of Curriculum Exam. Issue 1 (14th March 2022) - Massey, Scott; Chadha, Rajat; Campbell, Dana; Rodgers, Christine
Abstract : Purpose: To assess the value of the Physician Assistant Education Association's End of Curriculum exam TM and formative and summative exams during the physician assistant program in predicting Physician Assistant National Certifying Exam (PANCE) scores. Methods: Value of the End of Curriculum exam, Physician Assistant Clinical Knowledge Rating and Assessment Tool (PACKRAT I, PACKRAT II), PANCE simulation (SUMM I), and Objective Structured Clinical Examination in predicting future PANCE scores was assessed using correlation and regression analysis of data for 27 PA students from one cohort. Results: The End of Curriculum exam, PACKRAT I, PACKRAT II, and SUMM I are statistically significant predictors of PANCE score ( p < 0.01). A combination of PACKRAT I and PACKRAT II was the best predictor of PANCE score and explained a large amount of variance (77.0%) in PANCE scores. Conclusion: PAEA's End of Curriculum exam is one of the strongest predictors of PANCE score (r = 0.78). It offers an additional opportunity for programs to provide PA students with another layer of academic advising and to guide their preparation for PANCE.